Formation of students' subjectivity in the educational process of higher school - E. V. Medvedeva (Moscow Polytechnic University, 2022)
The key theme of the article is the systematic organization of the process of students'subjectivity formation in educational process at the university. This enables to achieve anorganic combination of the processes of development, training and upbringing of students, and to make education a purposeful process of personal and professional development ofstudents.